The effect of different solutions on solubility of different anterior restorative material - Ohud Sandougah; Nisrin Alharthi; Hossam Moussa (Saudi Dental Journal)
Since water sorption of any restorative material can result in expansion of the restoration, which would be deterimental to the restoration, it is important to limit the amount of water absorbed [1]. One of the most important shortcoming of dental composite is their degradation which lead to reduce mechanical and esthetic properties [2]. Objective: To evaluate the effect of different solutions on solubility of different anterior restorative material. Materials and method: Forty five cylindrical specimens of different restorative material (GIC – Bulk fill – Hybrid) Each fifteen samples. Each main Group was divide into three Groups according to the solution used (water – vinegar – redbull). We measure the solubility for each sample by weight before immersion in solution and after two weeks by using digital electronic balance. The result were statistically analyzed using ANOVA followed by student – Newman-Keruls post hoc test (p = 0,05). Result: All the restorative materials show increase solubility in all solution by the end of the two weeks except in red bull with hybrid composite. The GIC show highest solubility, while the bulk fill composite show the lowest solubility. In All the restorative material The water show the lowest solubility, while the red bull show the highest solubility. There is no significant difference between the recorded date of the vinegar and redbull. Conclusion: The best material for the patient drinks: A-Water: GIC, B-Vinegar:GIC, D-Redbull: Bulk fill composite.